2023
DOI: 10.1111/epi.17518
|View full text |Cite
|
Sign up to set email alerts
|

A region‐specific modulation of sleep slow waves on interictal epilepsy markers in focal epilepsy

Abstract: Objective Sleep strongly activates interictal epileptic activity through an unclear mechanism. We investigated how scalp sleep slow waves (SSWs), whose positive and negative half‐waves reflect the fluctuation of neuronal excitability between the up and down states, respectively, modulate interictal epileptic events in focal epilepsy. Methods Simultaneous polysomnography was performed in 45 patients with drug‐resistant focal epilepsy during intracranial electroencephalographic recording. Scalp SSWs and intracra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…By contrast, in the SOZ, ripple coupling and maximal ripple‐associated firing probability occurred during the late UP‐DOWN transition, which was different from the coupling and firing in the non‐SOZ (Kuiper's V, p = 1e–3). These results included regions with interictal epileptiform discharges as part of the non‐SOZ, whereas prior investigations included these regions as part of the SOZ 27,30,37 . Thus, in the SOZ, pathological ripples occur during the UP‐DOWN transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, in the SOZ, ripple coupling and maximal ripple‐associated firing probability occurred during the late UP‐DOWN transition, which was different from the coupling and firing in the non‐SOZ (Kuiper's V, p = 1e–3). These results included regions with interictal epileptiform discharges as part of the non‐SOZ, whereas prior investigations included these regions as part of the SOZ 27,30,37 . Thus, in the SOZ, pathological ripples occur during the UP‐DOWN transition.…”
Section: Resultsmentioning
confidence: 99%
“…These results included regions with interictal epileptiform discharges as part of the non-SOZ, whereas prior investigations included these regions as part of the SOZ. 27,30,37 Thus, in the SOZ, pathological ripples occur during the UP-DOWN transition.…”
Section: Hfos and Excitability During Hfos In The Soz And Non-soz Rel...mentioning
confidence: 99%
“…The AdTech electrodes used at the Hôpital de la Salpêtrière were equipped with 4-12 contacts, each measuring 1 mm in diameter, 2.41 mm in length, and spaced 5 mm apart (Lehongre et al, 2022). Meanwhile, the HKHS electrodes employed at the Second Affiliated Hospital of Zhejiang University consisted of 8-16 contacts, with a diameter of 0.8 mm, length of 2 mm, and an inter-contact distance of 1.5 mm (Chen et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al 36 found that IEDs and ripples were clustered around the negative peaks of sleep slow waves, and that the increase in IED and ripple densities were associated with an increase in sleep slow-wave amplitude. In addition, phase analysis showed that IEDs and ripples in the SOZ exhibited a similar facilitation by slow waves during the down state.…”
Section: The Bidirectional Relationship Between Sleep and The Interic...mentioning
confidence: 99%
“…Eight studies evaluated the association between physiological sleep events on IEDs or HFOs and are outlined in Table 4. 5,20,25,[36][37][38][39][40] Such physiological sleep events include slow waves and sleep spindles as observed in NREM sleep, phasic REM sleep, and sleep arousals.…”
Section: Association Between Sleep Microstructure and Interictal Acti...mentioning
confidence: 99%